2003
DOI: 10.1074/jbc.m305434200
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Orientation of Reconstituted Maltoporin Channels at the Single-protein Level

Abstract: Recently we have shown that maltoporin channels reconstituted into black lipid membranes have pronounced asymmetric properties in both ion conduction and sugar binding. This asymmetry revealed also that maltoporin insertion is directional. However, the orientation in the lipid bilayer remained an open question. To elucidate the orientation, we performed point mutations at each side of the channel and analyzed the ion current fluctuation caused by an asymmetric maltohexaose addition. In a second series we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
72
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 39 publications
6
72
0
1
Order By: Relevance
“…Inspection of the porin structure suggests that the permeation of molecules through the channel is driven by molecular interactions with the surface rather than by free diffusion 68,69 . The first evidence for facilitated diffusion through a binding site was found in maltoporin, a maltose-specific channel from the outer membrane in E. coli [70][71][72][73] . a closer look at the OmpF structure revealed that it possesses a possible affinity site for ampicillin molecules (FIG.…”
Section: Physico-chemical Basis Of Porin Transportmentioning
confidence: 99%
See 4 more Smart Citations
“…Inspection of the porin structure suggests that the permeation of molecules through the channel is driven by molecular interactions with the surface rather than by free diffusion 68,69 . The first evidence for facilitated diffusion through a binding site was found in maltoporin, a maltose-specific channel from the outer membrane in E. coli [70][71][72][73] . a closer look at the OmpF structure revealed that it possesses a possible affinity site for ampicillin molecules (FIG.…”
Section: Physico-chemical Basis Of Porin Transportmentioning
confidence: 99%
“…Addition of antibiotics or sugar molecules on one (or both) side of the bilayer causes them to diffuse towards the channel. High-resolution ion-current fluctuation analysis allows detection of the passage of single molecules and thus characterization of facilitated permeation of sugars and antibiotics [68][69][70] . Addition of millimolar concentrations of ampicillin to the system can cause fluctuations in the ion current.…”
Section: Box 3 | Electrophysiology Studiesmentioning
confidence: 99%
See 3 more Smart Citations